(untitled) (MAUSAM, 1951)
A demountable type of Torsion Seismograph based on the principle of the Torsion Seismograph of Wood and Anderson has been described. The model is easy to construct and gives satisfactory results for pendulum periods up to 6 seconds. A few records taken by the instrument are reproduced.